The receptor-associated protein (RAP) binds calmodulin and is phosphorylated by calmodulin-dependent kinase II. - Petersen, C M (1996)
The receptor-associated protein, RAP, is an intracellular protein that may function as a chaperone for the LDL-receptor family receptors. Here we report calmodulin as the first identified RAP binding protein outside of the LDL-receptor family members. We demonstrate that RAP binds calmodulin in a Ca2+- and pH-dependent manner characteristic of calmodulin-dependent enzymes, and present evidence that RAP is a substrate for calmodulin-dependent enzymes. Thus, CaM-kinase II and calcineurin readily phosphorylate and dephosphorylate, respectively, serine residues in RAP, and in the individual RAP domains D2 (amino acids 113-218) and D3 (amino acids 219-323) which both contain sites for CaM-kinase II-mediated phosphorylation and for calmodulin binding. In addition, we provide evidence that RAP is phosphorylated by other kinases such as casein kinase II. Studies of 32[ortho]P-labelled cell cultures demonstrate that RAP is phosphorylated in vivo. Our results suggest that RAP may have hitherto unknown functions implicating phosphorylation and calmodulin-mediated modulation.